2009
DOI: 10.1007/s10549-009-0534-7
|View full text |Cite
|
Sign up to set email alerts
|

Ki67: a time-varying biomarker of risk of breast cancer in atypical hyperplasia

Abstract: Uncontrolled proliferation is a defining feature of the malignant phenotype. Ki67 is a marker for proliferating cells and is overexpressed in many breast cancers. Atypical hyperplasia is a premalignant lesion of the breast (relative risk ~ 4.0). Here, we asked if Ki67 expression could stratify risk in women with atypia. Ki67 expression was assessed immunohistochemically by digital image analysis in archival sections from 192 women with atypia diagnosed at the Mayo Clinic 1/1/67–12/31/91. Risk factor and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 39 publications
3
58
1
1
Order By: Relevance
“…Recent studies have shown that Ki-67 LI in atypical hyperplasia predicts future breast cancer risk (11) and is associated with the progression of carcinogenesis from ductal hyperplasia to DIN (10,26). Moreover, Ki-67 LI after short-term presurgical treatment predicts recurrencefree and overall survival in women with early breast cancer, supporting the use of this biomarker to tailor adjuvant treatment and to screen drugs in a cost-effective manner (2-4, 27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that Ki-67 LI in atypical hyperplasia predicts future breast cancer risk (11) and is associated with the progression of carcinogenesis from ductal hyperplasia to DIN (10,26). Moreover, Ki-67 LI after short-term presurgical treatment predicts recurrencefree and overall survival in women with early breast cancer, supporting the use of this biomarker to tailor adjuvant treatment and to screen drugs in a cost-effective manner (2-4, 27).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the window-of-opportunity trial model can exploit the existence of the field cancerization, which is well documented in breast cancer (9), to get important clues on the preventive effect of the investigational agent. Moreover, recent studies have shown that Ki-67 LI is positively associated with carcinogenesis progression (10) and its level of staining in atypical lesions in core biopsies of nonmalignant lesions may predict subsequent breast cancer risk, going from a 10-year cumulative incidence of breast cancer of 3% for lesions with Ki-67 LI less than 2% to 14% in those with Ki-67 LI 2% or more (11).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of this marker was not significant in our study (p00.181), while Ki67 biomarker expression was highly significant (p00.001). Ki67 has been appeared as a time-varying biomarker of breast cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…These investigators carefully evaluated p16 ink4a expression by immunohistochemistry on excisional biopsies containing atypical hyperplasia from 233 women with long-term follow-up (median ¼ 14.5 years). They previously found significantly increased risk associated with elevated COX-2 and Ki67 in atypical hyperplasia in the same cohort (5,6). In the current study, however, they found no association between p16 ink4a and risk, whether considered alone, or in combination with COX-2 and Ki67.…”
mentioning
confidence: 84%